(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Denture cleanser should be designed to remove and prevent re accumulation of microbial plaque. Cleaning the denture by chemical immersion have several advantages that solutions reach all areas of the denture and results in complete cleaning. One problem associated with their use has been bleach and discoloration the surface layer of acrylic dentures. Objective: to assess the color alteration of heat polymerized acrylic resin after immersed in different types of chemical denture cleanser. Method: forty five rectangular specimens (50x3.5x3mm) (length-width-thickness) of heat activated acrylic resin were divided in three denture cleansers groups (sodium hypochlorite NaOCl 0.5%) and vinegar (acetic acid 6%) and control group (immersed in distal water). Soaking trial 8 hours simulated 30 days of use. Color alterations were assessed by visual examination of photographs and by spectrophotometer testing device. Results: the results of spectrophotometer testing device did not show any interaction between different type of chemical cleansers and acrylic resin during 30 days 8 simulated use, also visual examination did not detect any color alteration. Conclusion: denture clearers, when used according to the manufacturer’s instructions, did not cause any mechanical or visual alterations in the heat polymerized acrylic resin. Keywords: Acrylic resin – denture cleansercolor changes.